Development of a Stress Sensor for Solids - N. N. Trekin; E. N. Kodysh; S. D. Shmakov; A. B. Chaganov; A. V. Cherepanov (Железобетонные конструкции)
The paper presents the results of experimental design of a cortex of the embedded stress sensor, which allows to determine stresses in the cross-section of large-scale laboratory monolithic structures made on the basis of mineral and polymer binders (concrete, gypsum, etc.). The objectives of the design were to develop a constructive solution of the stress sensor housing based on strain gauges, which has small dimensions, low manufacturing cost, as well as high resolution and stability of readings over the entire sensitivity area (stress up to 400 kgf/cm2).The stress sensor allows to determine the stress in laboratory structures with high accuracy, without significantly affecting the stress-strain state of the section at different stages of operation of the structural element.